Exploring Methodological Decisions for Calculating the Minimally Detectable Change in Dysarthria: Reliability, Statistics, and Standard Error of Measurement. - Gates, Kelly E.; Mefferd, Antje S.; Stipancic, Kaila L. (Journal of Speech, Language & Hearing Research, 2025)
Purpose: The minimally detectable change (MDC), widely used in rehabilitation sciences to interpret changes in outcome measures, is calculated using a reliability method, reliability statistic, and standard error of measurement (SEM). This study examined how different methodological choices affect MDC thresholds of speech intelligibility in speakers with dysarthria. The goals of this study were to compare MDCs calculated using (a) three different reliability methods, (b) two different reliability statistics, and (c) three different SEM calculations. Method: Recordings of the Speech Intelligibility Test from 200 speakers including speakers with amyotrophic lateral sclerosis (n = 16), Huntington's disease (n = 44), multiple sclerosis (n = 60), and Parkinson's disease (n = 40), along with healthy controls (n = 40), were drawn from two databases. Thirty inexperienced listeners completed two sessions, providing orthographic transcriptions of 20 speakers. MDCs of intelligibility were calculated using (a) three reliability methods (i.e., test-retest, split-half, and intrarater), (b) two reliability statistics (i.e., Pearson r and intraclass correlation coefficients [ICCs]), and (c) three different formulas for calculating the SEM. Kruskal-Wallis tests were used to assess the effects of reliability methods, statistics, and SEM calculations. Results: Significant differences were found between the MDCs when using split-half and test-retest reliability, when using Pearson r and ICC, and when using two of the three SEM calculations. Conclusions: Results demonstrate that methodological decisions can impact MDCs of speech intelligibility in speakers with dysarthria, highlighting the need for specific, detailed reporting of methodology used to calculate MDCs in future work. Findings can provide methodological guidance for future studies and contextualize existing research on intelligibility changes.